Perlindungan Hukum Terhadap Pihak Debitur Akibat Kenaikan Suku Bunga Kredit Bank (Tinjauan Hukum Perlindungan Konsumen) - Didit Saltriwiguna (Fakultas Hukum Universitas Mulawarman, 2009)
Banks’ intermediary function and its funding collection from the community seem always accompanied with the funding provision in form of credit to be channeled to the credit applicants. Banks benefit from the credit interest. In the practice, the banks change (increase) credit interest rate paid by debtors. It leads to the juridical consequence due to its unsuitability to the credit agreement. At last, the debtors remain susceptible to loss. Guaranteeing the law protection and law certainty for the debtors losing for such unilateral action, the regulations of consumer protection, therefore, have important functions and effects to avoid from the arbitrary action of banks as the entrepreneurs